A combined approach using differential scanning calorimetry with polarized light thermomicroscopy in the investigation of ketoprofen and nicotinamide cocrystal - Perpétuo, G. L.; Chierice, G. O.; Ferreira, L. T. [UNESP]; Fraga-Silva, T. F.C. [UNESP]; Venturini, J. [UNESP]; Arruda, M. S.P. [UNESP]; Bannach, G. [UNESP]; Castro, R. A.E. (Elsevier, 2017)
A screening of ketoprofen cocrystal with nicotinamide as a coformer was performed using the Kofler contact method and mechanochemistry. The crystallization of KET (with cocrystal formation) can occur during the heating process. However, although it is thermodynamically favorable, it was found that the kinetic reactions were slow, since the KET crystallization took about 30 days. The compounds obtained were analysed by differential scanning calorimetry (DSC), polarized light thermomicroscopy (PLTM), Fourier transform infrared spectroscopy (FTIR), and X-ray powder diffraction (XRPD). Cocrystal formation between ketoprofen and nicotinamide has great interest because the nicotinamide has FDA/GRAS status. At the adopted conditions, the achievement of cocrystal between ketoprofen and nicotinamide was not possible by mechanochemical methods However, experiments conducted by the Kofler method confirmed that ketoprofen interacted, under determined conditions, with nicotinamide giving rise to a new cocrystal. Furthermore, biological tests revealed that the KET + NA (1:1) eutectic system obtained by grinding had a greater anti-inflammatory action when compared to pure ketoprofen.
Keywords: Cocrystal; Ketoprofen; Nicotinamide; Thermomicroscopy